Design of L1 adaptive controllers for human patient anesthesia. (November 2015) - Kharisov, Evgeny; Beck, Carolyn L.; Bloom, Marc
Abstract: In this paper, the development and implementation of L 1 adaptive control designs for anesthesia delivery to patients in surgical settings is presented. Our main objectives are the design of model-based feedback controllers ensuring that the patient׳s bispectral index profile tracks a prespecified reference trajectory, and demonstrates robustness to inter-patient variability. Patient models are constructed based on clinical trial data and gray box system identification methods. Controller switching mechanisms and specific safety measures are considered in the design and discussed in the paper. Simulation results are provided, demonstrating the effectiveness of the control methods.